Peningkatan Kesejahteraan Mental Siswa melalui Bimbingan Konseling Islam - Eko Carles; Zepri Hiptraspa; Idi Warsah; M Supperapto Effendi (Islamic Counseling: Jurnal Bimbingan dan Konseling Islam, 2023)
This study aims to describe the phenomenon of improving the mental well-being of MTS Tarbiyah Curup students through Islamic counseling. This study used a qualitative approach with a descriptive research type and was conducted using data collection techniques through in-depth interviews with students, counseling teachers and school principals, participant observation, and documentation studies. Data were analyzed by inductive approach and thematic analysis techniques. Research is carried out by ensuring research ethics are met by obtaining permission from the school and research subjects, maintaining data confidentiality, and providing clear and accurate information to research subjects regarding the aims and benefits of research. Islamic counseling guidance provides significant benefits for the mental well-being of students. The students who received Islamic counseling felt calmer, excited and optimistic about their future. Islamic counseling guidance also helps students to reduce stress and improve their ability to deal with problems and conflicts. In addition, Islamic guidance and counseling motivates students to study better and improve their overall academic performance. The implication of this research is the importance of paying attention to students' mental well-being and the importance of Islamic guidance and counseling as a strategy in improving students' mental well-being in schools.